The Role of Benefit Perception in Mediating the Influence of Ease of Use and Security on Qris Usage Decisions - Ranti Pradita; Aang Curatman (Interdisciplinary Social Studies, 2026)
The development of digital payment systems supports the increase in the use of QRIS, especially among Generation Z. This research aims to examine the influence of ease of use and transaction security on QRIS usage decisions, as well as testing the role of benefit perception as a mediating variable. A quantitative approach with an associative study design was used. Primary data was collected through a questionnaire administered to 168 Generation Z respondents who use QRIS in Cirebon City, using purposive sampling techniques. Data analysis was conducted using SEM-PLS with the help of SmartPLS. The results of the study show that ease of use and transaction security have a positive and significant influence on the decision to use QRIS. These two variables also positively influence the perception of benefits. The perception of benefits has been proven to have a significant effect on the decision to use QRIS and is able to mediate the influence of ease of use and transaction security on the decision to use. These findings indicate that the decision to use QRIS is influenced by a combination of convenience, security, and the benefits that users perceive. This research contributes to economic growth by promoting digital payment adoption, transaction efficiency, and financial inclusion. Its novelty lies in testing benefit perception as a mediating variable in an integrated model of Generation Z's QRIS usage at the regional level.